Characterization of Pseudomonas consortia isolated in sediments of the Estero Salado in the northern sector of Guayaquil - Muñoz Cajiao, Carlos Alberto; Dueñas Muñoz, Winter Enrique; Vizueta Lucero, Steven Jair (Ingeniería Química y Desarrollo, 2022)
There are many open research fronts to solve the pollution problem of the estuary of Estero Salado in the city of Guayaquil, carried out in-situ, where they aim to reduce hydrocarbon contamination through bioremediation methods, including bioaugmentation methods. of endogenous microorganisms, however, are not optimal study conditions, so we set out to characterize the capacity of these organisms to degrade hydrocarbons under controlled environments, where we proceeded to take a sample of sandy and rocky soil, both studied in triplicate, to later extract from them bacterial consortiums, increasing their population and determining by means of infrared spectrophotometry the changes produced in the concentrations of total petroleum hydrocarbons (TPH) before and after introducing the bio-increased consortia, presenting optimal results in the Attachment after the respective statistical analysis that show a reduction of 90% under controlled conditions the levels of TPH in the different treatments